MANAJEMEN PEMBIAYAAN PENDIDIKAN DALAM UPAYA PENINGKATAN MUTU AKADEMIK MI NEGERI 2 SEMARANG - Sri Rusmiyati; Noor Miyono; Sumarno (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The research background at MI Negeri 2 Semarang as a place for research, because MI Negeri 2 Semarang has a clear mechanism in accordance with the SOP (Implementation Operational Standards) for financing management that is transparent and accountable to the public, both to the community and the authorities; in developing the academic quality of MI Negeri 2 Semarang guided by the National Education Standards (SNP) and madrasa quality assessment based on AKM scores in the field of literacy and numeracy; MI Negeri 2 Semarang has a madrasa development plan to realize the vision, mission and goals of the madrasa; and The accuracy of financing management in improving academic quality at MI Negeri 2 Semarang can be seen from the various academic achievements achieved by teachers and students. The focus of the research is the process of implementing education financing management in an effort to improve academic quality at MI Negeri 2 Semarang which meets the financing principles, namely 1) Transparency in implementing educational financing management at MI Negeri 2 Semarang in improving academic quality, 2) Accountability for implementing MI education financing management Negeri 2 Semarang in improving academic quality, 3) Effectiveness of implementation of educational financing management at MI Negeri 2 Semarang in improving academic quality, 4) Efficiency of implementing educational financing management at MI Negeri 2 Semarang in improving academic quality. This research is field research with a qualitative approach. Data collection was carried out using observation, interviews and document search methods. Checking the validity of the data using source triangulation techniques and technical triangulation in its implementation. The results of this research explain that the implementation of education financing management in an effort to improve academic quality at MI Negeri 2 Semarang is by applying the principles of transparency, accountability, effectiveness and efficiency which are realized in the form of easy access to information regarding the management of madrasah education financing both offline and online, involving stakeholders in decision making, open reporting on the use of education funds, and collaboration between related parties to improve the academic quality of madrasas. The implementation of education financing management is running well and in accordance with procedures. The results of the analysis of madrasa academic quality show that there is a correlation with financing management where financing management is able to answer programs and policies that support improving academic quality at MI Negeri 2 Semarang. Keywords: management, education financing, academic quality